Effect of an Active Video Game Intervention Combined With Multicomponent Exercise for Cardiorespiratory Fitness in Children With Overweight and Obesity: Randomized Controlled Trial - Cristina Comeras-Chueca; Lorena Villalba-Heredia; Jose Luis Perez-Lasierra; Gabriel Lozano-Berges; Angel Matute-Llorente; German Vicente-Rodriguez; Jose Antonio Casajus; Alex Gonzalez-Aguero (JMIR Publications, 2022)
BackgroundChildhood overweight and obesity have become major global health problems and are negatively related with the cardiorespiratory fitness (CRF) level in school children and adolescents. Exercise, specifically multicomponent training, is effective for CRF improvement, but the main challenge is to ensure adherence to exercise in children with overweight and obesity. Therefore, new ways of exercising that are more attractive and motivational for this population are needed and playing or training with active video games (AVGs) has been proposed as an effective alternative because they require full-body movement and therefore increase energy expenditure. ObjectiveThe main aim of this study was to investigate the effects of an AVG intervention combined with multicomponent training on CRF at maximal and submaximal intensities in children with overweight or obesity. MethodsWe recruited 28 children (13 girls and 15 boys) aged 9 to 11 years with overweight or obesity from medical centers and divided them into 2 groups, an intervention group (n=20) that participated in a 5-month supervised AVG exercise program combined with multicomponent exercise, and a control group (n=8) that continued daily activities without modification. A maximal stress test to measure CRF using a walking-graded protocol with respiratory gas exchange was performed by the participants. ResultsThe AVG group showed a significant decrease in heart rate and oxygen uptake for the same intensities in the submaximal stages of the maximal treadmill test, as well as a lower oxygen uptake percentage according to the individual maximal oxygen uptake, whereas the control group did not show overall changes. No change in the peak oxygen uptake (VO2peak) was found. ConclusionsA 5-month AVG intervention combined with multicomponent exercise had positive effects on CRF at submaximal intensity, showing a lower heart rate and oxygen uptake at the same intensities and displaying a lower oxygen uptake percentage according to the individual (VO2peak). Greater benefits were found in children with the highest fat percentage. Trial RegistrationClinicalTrials.gov NCT04418713; https://clinicaltrials.gov/show/NCT04418713